The Role of Children in Managing Family Finances in Chinese Tradition - Natasha Angela; Elga Yulindisti; Elok Heniwati (JURNAL ECONOMINA, 2026)
This study aims to understand children's involvement in Chinese family financial management, including the forms of involvement, influencing factors, the role of cultural values, and their impact on family financial dynamics and efficiency. The study employed a qualitative method with a case study approach. Data were obtained through observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research results show that children not only play a role as recipients of money, but are also actively involved in recording expenses, preparing budgets, and monitoring the family's financial situation. This involvement is influenced by Chinese cultural values that emphasize thrift, discipline, and responsibility. In addition to cultural factors, children's self-awareness and their parents' circumstances and needs also determine their level of participation in family financial management. This involvement has a positive impact in the form of increased transparency and efficiency of financial management, while strengthening communication and openness within family relationships. Furthermore, children's participation serves as an effective financial education tool, fostering independence, responsibility, and financial decision-making skills from an early age. These findings suggest that children's involvement can be an important strategy in supporting the sustainability of family financial management.